2009
DOI: 10.1155/2009/382695
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Transceiver Architectures for 60 GHz Ultra Wideband WLANs

Abstract: Recommended by Daniel IancuMillimeter-wave multiport transceiver architectures dedicated to 60 GHz UWB short-range communications are proposed in this paper. Multi-port circuits based on 90• hybrid couplers are intensively used for phased antenna array, millimeter-wave modulation and down-conversion, as a low-cost alternative to the conventional architecture. This allows complete integration of circuits including antennas, in planar technology, on the same substrate, improving the overall transceiver performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Their use in the satellite context is undoubtedly an innovative approach. This type of waveforms could bring some substantial advantages in the direction of relaxing HW requirements and reducing systems costs [12], with the disadvantage of a reduced spectral efficiency. Several works have demonstrated that IR-UWB at EHF, namely at 60 GHz band, can provide transceiver simplicity, i.e.…”
Section: Impulse-based Uwb Waveformsmentioning
confidence: 99%
“…Their use in the satellite context is undoubtedly an innovative approach. This type of waveforms could bring some substantial advantages in the direction of relaxing HW requirements and reducing systems costs [12], with the disadvantage of a reduced spectral efficiency. Several works have demonstrated that IR-UWB at EHF, namely at 60 GHz band, can provide transceiver simplicity, i.e.…”
Section: Impulse-based Uwb Waveformsmentioning
confidence: 99%
“…One way to satisfy the requirements mentioned above is the use of ultra-wideband communication (UWB) [2], which is a potential candidate for short-range multiple access wireless communication applications, including indoor static wireless local area networks, decentralized multiple access communication and secure military applications [3]. Additionally, wireless fiber communication networks operating at mm-wave frequencies have been considered for delivering broadband multimedia services to mobile terminals [7]. The multiband (MB) UWB spectrum is split into a number of sub-bands, which allows the use of narrowband techniques within each subband.…”
Section: Introductionmentioning
confidence: 99%